Copy number variation of LINGO1 in familial dystonic tremor. (4th February 2019) - Alakbarzade, Vafa; Iype, Thomas; Chioza, Barry A.; Singh, Royana; Harlalka, Gaurav V.; Hardy, Holly; Sreekantan-Nair, Ajith; Proukakis, Christos; Peall, Kathryn; Clark, Lorraine N.; Caswell, Richard; Lango Allen, Hana; et al.
Abstract : Objective: To elucidate the genetic cause of a large 5 generation South Indian family with multiple individuals with predominantly an upper limb postural tremor and posturing in keeping with another form of tremor, namely, dystonic tremor. Methods: Whole-genome single nucleotide polymorphism (SNP) microarray analysis was undertaken to look for copy number variants in the affected individuals. Results: Whole-genome SNP microarray studies identified a tandem duplicated genomic segment of chromosome 15q24 present in all affected family members. Whole-genome sequencing demonstrated that it comprised a ∼550-kb tandem duplication encompassing the entire LINGO1 gene. Conclusions: The identification of a genomic duplication as the likely molecular cause of this condition, resulting in an additional LINGO1 gene copy in affected cases, adds further support for a causal role of this gene in tremor disorders and implicates increased expression levels of LINGO1 as a potential pathogenic mechanism.